2017
DOI: 10.1007/s10549-017-4389-z
|View full text |Cite|
|
Sign up to set email alerts
|

Contribution of clinical and socioeconomic factors to differences in breast cancer subtype and mortality between Hispanic and non-Hispanic white women

Abstract: Purpose To assess tumor subtype distribution and the relative contribution of clinical and sociodemographic factors on breast cancer survival between Hispanic and non-Hispanic whites (NHW). Methods We analyzed data from the California Cancer Registry, which included 29,626 Hispanic and 99,862 NHW female invasive breast cancer cases diagnosed from 2004–2014. Logistic regression was used to assess ethnic differences in tumor subtype, and Cox proportional hazard modeling to assess differences in breast cancer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…Several studies have identified an increased proportion of basal-like breast cancers in populations of African ancestry (57)(58)(59)(60)(61). Increased frequency of TNBC has also been observed in the Hispanic/Latino population (62)(63)(64)(65)(66)(67)(68), American Indian/Alaska Native population (64), and women from the Indian subcontinent (69). Interestingly, Filipino women were least likely to have TNBC (69), suggesting a broad range of variability.…”
Section: Ancestral-related Health Disparities In Cancer: Breast Cancermentioning
confidence: 99%
“…Several studies have identified an increased proportion of basal-like breast cancers in populations of African ancestry (57)(58)(59)(60)(61). Increased frequency of TNBC has also been observed in the Hispanic/Latino population (62)(63)(64)(65)(66)(67)(68), American Indian/Alaska Native population (64), and women from the Indian subcontinent (69). Interestingly, Filipino women were least likely to have TNBC (69), suggesting a broad range of variability.…”
Section: Ancestral-related Health Disparities In Cancer: Breast Cancermentioning
confidence: 99%
“…Multiple studies have shown that while Hispanics/Latinas (Latinas) have lower breast cancer incidence and mortality rates than non-Hispanic White women, they have a higher risk of breast cancer-specific mortality with hazard ratio (HR) estimates ranging from 1.1 to 1.3 (3)(4)(5)(6)(7). This disparity could be in part explained by the fact that Latinas are more likely to be diagnosed with the more aggressive HER2 þ and hormone receptornegative subtypes of the disease than non-Hispanic White women (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Racial disparities in survival may be attributed to both biologic (eg, subtype, tumor characteristics, molecular abnormalities that accelerate progression) and non-biologic factors (eg, socioeconomic status, insurance coverage). [7][8][9] Although recurrence risk by breast cancer subtypes has been examined, surprisingly few studies have included adequate numbers of minority women, particularly from Asian subgroups, precluding evaluation of potential racial/ethnic disparities by biologic subtypes. Previous studies that examined racial/ethnic disparities in breast cancer prognosis were limited by small numbers of breast cancer events, 10 or lacked comprehensive information on breast cancer therapy.…”
Section: Introductionmentioning
confidence: 99%